Hypertext- and linear text-based student papers as indices of critical thinking - Muega, Michael Arthus G. (2003)
The purpose of this study was to determine the effects of contextualization, differentiation and visualization instructional approaches on students' computer skills using Microsoft User Specialist Certification Test in Microsoft Access. Eighty nine first year college students majoring in Management Information Science and Computer Information Technology participated in the study. Findings revealed that differentiation instructional approach was found to produce significant difference in achievement compared with the conventional teaching method. The second most effective approach was contextualization followed by visualization. In addition, mother's education was found to be the best predictor of a student's skills in using computer.
Thesis (Ph.D. History & Philosophy of Education)--University of the Philippines, Diliman.
Keywords: Critical thinking -- Philippines -- Diliman (Quezon City).; Computer network resources -- Evaluation. -- Philippines -- Diliman (Quezon City); Library resources -- Evaluation. -- Philippines -- Diliman (Quezon City); Internet research -- Philippines -- Diliman (Quezon City).; College students -- Philippines -- Diliman (Quezon City).